Effectiveness of a polyhexanide irrigation solution on methicillin‐resistant Staphylococcus aureus biofilms in a porcine wound model. Issue 6 (7th March 2017) - Davis, Stephen C; Harding, Andrew; Gil, Joel; Parajon, Fernando; Valdes, Jose; Solis, Michael; Higa, Alex
Abstract: Irrigation and removal of necrotic debris can be beneficial for proper healing. It is becoming increasingly evident that wounds colonized with biofilm forming bacteria, such as Staphylococcus aureus (SA), can be more difficult to eradicate. Here we report our findings of the effects of an irrigation solution containing propyl‐betaine and polyhexanide (PHMB) on methicillin‐resistant Staphylococcus aureus (MRSA) biofilms in a porcine wound model. Thirty‐nine deep partial thickness wounds were created with six wounds assigned to one of six treatment groups: (i) PHMB, (ii) Ringer's solution, (iii) hypochlorous acid/sodium hypochlorite, (iv) sterile water, (v) octenidine dihydrochloride, and (vi) octenilin. Wounds were inoculated with MRSA and covered with a polyurethane dressing for 24 hours to allow biofilm formation. The dressings were then removed and the wounds were irrigated twice daily for 3 days with the appropriate solution. MRSA from four wounds were recovered from each treatment group at 3 days and 6 days hours after initial treatment. Irrigation of wounds with the PHMB solution resulted in 97·85% and 99·64% reductions of MRSA at the respective 3 days and 6 days assessment times when compared to the untreated group. Both of these reductions were statistically significant compared to all other treatment groups ( P values <0·05).